Governance of Genetic Resources and Traditional Agricultural Knowledge in Colombia: A Food Sovereignty Approach - Vargas-Chaves, Iván; López-Oliva, José; Luna-Galván, Mauricio; Vargas-Chaves, Iván; López-Oliva, José; Luna-Galván, Mauricio; Vargas-Chaves, Iván; López-Oliva, José; Luna-Galván, Mauricio (Corporación Universitaria Americana, 2026)
Introduction: Although food sovereignty depends largely on control of agrobiodiversity and traditional knowledge, Colombia faces significant threats, such as biodiversity loss, dependence on commercial seeds, and unregulated bioprospecting. Objective: This article analyzes the relationship between genetic resource governance and food sovereignty in Colombia. Methodology: Through qualitative documentary analysis, this research evaluates how current agricultural policies and regulatory frameworks impact genetic diversity and the country’s ability to achieve autonomous food security. Results: The results reveal that traditional knowledge systems are fundamental to local adaptation, in situ conservation, and community empowerment; therefore, their erosion and biopiracy directly threaten these fundamental pillars. Conclusions: The analysis demonstrates that a governance model that prioritizes sustainable use and local control of genetic resources, together with the recognition of farmers’ rights, is essential to strengthening food sovereignty. Ultimately, the article advocates for legal reforms that integrate an “ecology of knowledge,” fostering dialogue between scientific and traditional systems to build resilient food systems for all Colombians.